High-intensity statin therapy yields better outcomes in acute coronary syndrome patients: a meta-analysis involving 26,497 patients - Yu, Shiyong (Lipids Health Dis, 2020)
BACKGROUND: Whether high-intensity statin treatment provides more clinical benefits compared with standard statin regimens in acute coronary syndrome (ACS) patients remains controversial. This meta-analysis aimed to comparatively assess high-intensity and standard statin regimens for efficacy and safety in patients with ACS. METHODS: The PubMed, EMBASE, and Cochrane Library databases were searched for studies assessing high-intensity vs. standard statin regimens for ACS treatment from inception to April 2020. The publication language was limited to English, and 16 randomized controlled trials were finally included in this study, with a total of 26,497 patients. RESULTS: Compared to the standard statin regimens, the relative ratio (RR) of major adverse cardiovascular events (MACE) in ACS patients treated by high-intensity statin was 0.77 (95%CI, 0.68–0.86; P < 0.00001; prediction interval, 0.56–1.07). In subgroup analysis, high-intensity statin therapy resulted in more clinical benefits regarding MACE compared with standard statin treatment in both Asian (RR = 0.77; 95%CI, 0.61–0.98; P = 0.03) and non-Asian (RR = 0.79; 95%CI, 0.71–0.89; P < 0.0001) patients. Although adverse events were acceptable in patients with ACS administered high-intensity statin therapy, this treatment was associated with a higher rate of adverse events (4.99% vs. 2.98%), including myopathy/myalgia and elevated liver enzymes, as reflected by elevated serum aminotransferase or aminotransferase amounts. CONCLUSION: The current findings indicated that high-intensity statin therapy might be beneficial in patients with ACS, and close monitoring for adverse effects should be performed.